(untitled) (Global Journal of Management and Business Research, 2014)
As time goes by Consumers tend to be more aware about the environment and this have changed their attitude and perceptions towards the environment. The fact that consumers are exposed to open information about the harmful products and their long term effects on the environment, this has affected their purchasing decision, and not to mention that consumers are stepping forward towards the greener products as marketers are using different strategies to persuade them to buy products that are considered to be environmentally-friendly. Ecological issues are still the major concern toward the whole world and people. Air contamination, deforestation and greenhouse impacts are the major natural issues that have happened till now alongside the activities of a person. In fact, consumers’ concerns about the environment have encouraged the marketers to change their strategies and adopt a marketing strategy called "Green marketing". So this research focuses on what makes green marketing successful, consumers’ behavior and their perceptions towards green products, the reason why marketers decided to adopt green marketing and how marketers can implement the green marketing mix.